Course and results of testing a suspended composite structure/Kabamosios betonšerdės konstrukcijos bandymo eiga ir rezultatai - Šaraškinas, Viaceslavas; Kvedaras, Audronis Kazimieras (Journal of Civil Engineering and Management, 2000)
Testing a suspended roof structure has been performed. The span of construction is 10.65 m, the support height 2.60 m. Element supports are pins. Joint between elements in the middle of span is a pin, too. Structural elements were made from steel tubes with hollow concrete core. The thickness of the tube wall 1.60 mm, and a concrete core wall about 20 mm. The length of elements 5.35 m. The tested roof structure was loaded with 8 vertical loads. The strain distribution in 3 sections of the composite elements was analysed. In seven points of the structure, vertical deflections were measured. The horizontal reaction was measured too as it is shown in Fig 10. Additionally, horizontal deflections of columns were controlled by 3 indicatory tenzometers. The roof structure resistance was analysed and indicated loads of the ultimate and the serviceability limit states were reached. During the test, the serviceability limit state was reached under the load of 3,40 kN/m. The vertical deflection at the ¼ of span exceeded L/300, the ultimate value for member under asymmetrical loading. Failure occured under the load of 9,80 kN/m, when one of the composite roof elements collapsed close to its supporting zone at a distance of about 1 m from the support. The normal stress of this cross-section reached the value of steel tensile strength. An experimental ultimate load is by about 27% less than the theoretical one determined for flexural member. Investigation shows the developed equipment and applied methods being useful for testing suspended structures of final flexural stiffness made from straight concrete-filled steel tubular members. It has been finalised that overall behaviour of the tested structure is very close to that of straight suspension steel members of final flexural stiffness. It has been experimentally determined that the failure load łą 9.80 kN/m was achieved when total tension strength of the external steel shell was used up. The presented value is greater than the ultimate one calculated only for the flexural member. Because composite members of the suspended structure are not only flexural but also tensional ones, it is necessary, for prediction of their limit state, to take into account the interaction between both components of composite cross-section (external steel shell and hollow concrete core) under such loading conditions. Article in Lithuanian. First Published Online: 26 Jul 2012